Excess of polyamine as a factor influencing the mode of coordination in the Eu(III)/α-hydroxy acid/spermine system. (15th July 2022) - Frymark, Justyna; Zabiszak, Michał; Grajewski, Jakub; Hnatejko, Zbigniew; Kołodyńska, Dorota; Kaczmarek, Małgorzata T.; Jastrzab, Renata
Graphical abstract: The complexes of europium(III) ions in binary and ternary systems with α-hydroxy acids and spermine were investigated. Coordination in the systems studied was confirmed by spectroscopic methods such as infrared spectroscopy, luminescence, and circular dichroism. The results confirmed the appearance of noncovalent interactions of protonated spermine with coordinated α-hydroxy acid. Abstract: The complexes of europium(III) ions in binary and ternary systems with α-hydroxy acids and biogenic amine - spermine were investigated. Studies have been performed in aqueous solution using the potentiometric method with computer analysis of the data. Analysis of the equilibrium constants of the reactions and spectroscopic data have allowed us to determine the type of coordination and effectiveness of the carboxyl groups in the process of complex formation in the systems studied. Furthermore, the results confirmed the occurrence of non-covalent interactions of protonated spermine with coordinated α-hydroxy acid. The effect of biogenic polyamine concentration was clearly confirmed, and their influence on the stability and coordination mode of ternary complexes was found.